Social representations about the family in intergenerational transmission: a teoretical aspect /Социальные представления о семье в межпоколенной трансмиссии: теоретический аспект - PODBORSCHI Angela (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
The article examines the issues of intergenerational transmission in the context of changing social representations about the family. It is shown a theoretical review of research on the topic of social representations about the family and the mechanisms of intergenerational transmission. The coincidence of a person’s values with the values of his group contributes to an increased sense of well-being and strengthens ties in the group, in this case, in the family. As a result of research, certain differences and similarities in the hierarchy of values of different generations are highlighted. The family occupies a place in the list of the main values.